Concentrations of urinary neopterin, but not suPAR, positively correlate with age in rhesus macaques - Cooper, Eve B.; Watowich, Marina M.; Beeby, Nina; Whalen, Connor; , Cayo Biobank Research Unit; Montague, Michael J.; Brent, Lauren J. N.; Snyder-Mackler, Noah; Higham, James P. (Frontiers in Ecology and Evolution, 2022)
Identifying biomarkers of age-related changes in immune system functioning that can be measured non-invasively is a significant step in progressing research on immunosenescence and inflammaging in free-ranging and wild animal populations. In the present study, we aimed to investigate the suitability of two urinary compounds, neopterin and suPAR, as biomarkers of age-related changes in immune activation and inflammation in a free-ranging rhesus macaque (Macaca mulatta) population. We also investigated age-associated variation in gene transcription from blood samples to understand the underlying proximate mechanisms that drive age-related changes in urinary neopterin or suPAR. Neopterin was significantly positively correlated with age, and had a moderate within-individual repeatability, indicating it is applicable as a biomarker of age-related changes. The age-related changes in urinary neopterin are not apparently driven by an age-related increase in the primary signaler of neopterin, IFN-y, but may be driven instead by an age-related increase in both CD14+ and CD14− monocytes. suPAR was not correlated with age, and had low repeatability within-individuals, indicating that it is likely better suited to measure acute inflammation rather than chronic age-related increases in inflammation (i.e., “inflammaging”). Neopterin and suPAR had a correlation of 25%, indicating that they likely often signal different processes, which if disentangled could provide a nuanced picture of immune-system function and inflammation when measured in tandem.